Demographic and epidemiological determinants of healthcare costs in Netherlands: cost of illness study. Issue 7151 (11th July 1998) - Meerding, Willem Jan; Bonneux, Luc; Polder, Johan J; Koopmanschap, Marc A; van der Maas, Paul J
Abstract: Objectives : To determine the demands on healthcare resources caused by different types of illnesses and variation with age and sex. Design: Information on healthcare use was obtained from all 22 healthcare sectors in the Netherlands. Most important sectors (hospitals, nursing homes, inpatient psychiatric care, institutions for mentally disabled people) have national registries. Total expenditures for each sector were subdivided into 21 age groups, sex, and 34 diagnostic groups. Setting: Netherlands, 1994. Main outcome measures: Proportion of healthcare budget spent on each category of disease and cost of health care per person at various ages. Results: After the first year of life, costs per person for children were lowest. Costs rose slowly throughout adult life and increased exponentially from age 50 onwards till the oldest age group (95). The top five areas of healthcare costs were mental retardation, musculoskeletal disease (predominantly joint disease and dorsopathy), dementia, a heterogeneous group of other mental disorders, and ill defined conditions. Stroke, all cancers combined, and coronary heart disease ranked 7, 8, and 10, respectively. Conclusions: The main determinants of healthcare use in the Netherlands are old age and disabling conditions, particularly mental disability. A large share of the healthcare budget is spent on long term nursing care, and this cost will inevitably increase further in an ageing population. Non-specific cost containment measures may endanger the quality of care for old and mentally disabled people.